The Influence of Corporate Social Responsibility, Chief Executive Officer Narcissism on Financial Performance with Earnings Management as a Mediator - Endang Kartini Situmorang, Jesenia; Indrati, Menik (Journal Research of Social Science, Economics, and Management, 2025)
This study investigates the effect of Corporate Social Responsibility (CSR) and Chief Executive Officer (CEO) narcissism on corporate financial performance, with earnings management serving as a mediating variable. The objectives are to analyze the direct effects of CSR and CEO narcissism on financial performance, measured by Return on Assets (ROA), examine their influence on earnings management practices, and test the mediating role of earnings management in these relationships. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, using data obtained from annual reports. Path analysis is employed to assess both the direct and indirect relationships among variables. Using a quantitative approach with path analysis, this study investigates 25 energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024, resulting in 75 observations through purposive sampling. The findings reveal that CSR has a significant positive influence on earnings management and directly contributes to improved financial performance, as measured by Return on Assets (ROA). CEO narcissism, while negatively associated with earnings management, demonstrates a significant positive impact on ROA. Additionally, earnings management plays a significant mediating role in the relationship between both CSR and ROA, as well as CEO narcissism and ROA. These results highlight the strategic role of CSR and the psychological traits of top executives in shaping financial outcomes. The study underscores the importance for stakeholders to consider managerial personality and social responsibility initiatives when evaluating a company’s financial health and governance practices.